Futures of a Complex World : Proceedings of the Conference “Futures of a Complex World”, 12–13 June 2017, Turku, Finland - Saarimaa, Riikka (ed.); Wilenius, Markku (ed.) (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
”Futures of a Complex World” conference 2017 was a success by all standards. We got record amount of participants - 330 experts from 29 countries - with fascinating array of topics from future of agriculture to new modeling tools. This publication, based on papers presented in the conference, is a token of the fascinating variety of approaches we can adopt while penetrating the future with the tools of our research. As such, it also represents in a splendid way the complexity of our world, embedded with grand challenges as well as fascinating new developments. Complexity science itself proves us that we need particularly two capacities to thrive in the ever more complex world: on the one hand we need to build more resilience into our systems, on the other, we should create new capacities to transform, if necessary. Both aspects are well represented in the articles of this publications.